Industrial training report: Park Avenue Hotel / Norhanim Abu Seman - Abu Seman, Norhanim (Perpustakaan Tengku Anis, 2017)
The industrial training duration based on the period from 1st February 2017 until 30th June 2017 in Electronic Data Processing Department at The Park Avenue Hotel at Sungai Petani, Kedah Darul Aman. The training consumes 5 month in one the department. The trainee have been explores a lot of new things and environment. The trainee has been exposed to technical and networking environment of working. The trainee has been assigns the project to develop new system which is Application Leave System. The trainee has been exposed to the systems that have been used in the department which are Property Management System (PMS) and Epitome Property Management System. The Electronic Data Processing Department is a well department that allows the trainee to explore a lot of things with their guidance. The staffs have a lot of experiences that they have in managing their work at the department.